Reimagining Masculinity: Perceptions of Male Support Among Married Women in Luwero District, Uganda - Priscillie Kankindi; Charles Edaku; Michael Mawa (International Journal of Global Health, 2025)
Background Masculinity remains a dominant phenomenon in the social construction and performance of male roles in society, influencing economic participation, access to essential services, and decision-making at household levels. Research focusing on women's empowerment has been extensively done, with little focus on how masculine support from men impacts the well- being of married women. This study examined how married women perceive male support in the context of economic, emotional, and physical support in Luwero district, Uganda. Methods This was an exploratory qualitative study conducted among married women aged 18 to 49 years. Key informant interviews were conducted with community women aged 30 to 40 years, and village health teams aged 30 to 40 years. The study participants were purposively selected based on the inclusion criteria of the study. Data were analysed using content analysis and the findings were presented using themes/sub-themes along with participant quotes. Results We interviewed married women aged 18 to 49 years old, with the majority falling in the age category of 30 to 39 years (59.1%) and were married for over 6 to 9 years (45.5%). Concerning the key informants, 2 VHTs were aged between 30 to 39 years (66.7%), and the women leaders were aged between 30 to 40 years (60%). About male support among women, nine subthemes emerged, including low engagement in family affairs, lack of financial support and cultural traditions, women’s insecurity, emotional neglect, women as providers of emotional support, lack of emotional responsiveness, emotional support driven by institutional policy, shared domestic responsibilities, and lack of physical presence during sickness. Generally, male support towards women was found to be lacking. Conclusion Male support among married women remains insufficient, contributing to emotional strain and unequally distributed responsibilities. Strengthening community awareness and engaging men through tailored programs can foster a more supportive domestic environment.
Keywords: Masculinity